Conductive binder and method for producing the same, electrode slurry, electrode, and lithium ion battery
Patent Information
- Application Number
- CN202610804082.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-06-05
AI Technical Summary
高容量硅材料在锂离子电池充放电过程中因体积变化导致的活性物质颗粒粉化和脱落,破坏电极的整体结构完整性,现有技术无法有效缓解的问题是如何在硅基负极电池的循环稳定性和倍率性能。
A modified carbon material is generated by acylation reaction of carboxylated carbon material and vinyl compound. It is then formed by in-situ polymerization with acrylic monomers to form a covalently linked conductive-adhesive integrated network. The conductive network and the polymer are connected by chemical bonds to form a three-dimensional interpenetrating network, which works together to reduce volume expansion through elastic deformation.
It effectively alleviates the volume expansion of silicon-based anode batteries during charge and discharge, improves the cycle stability and rate performance of the electrodes, reduces the irreversible consumption of electrolyte, and improves the first coulombic efficiency.
Smart Images

Figure CN122381740B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to conductive binders and their preparation methods, electrode slurries, electrodes, and lithium-ion batteries. Background Technology
[0002] With the rapid development of electric vehicles and portable electronic devices, the market has placed higher demands on the energy density of lithium-ion batteries. New-generation high-capacity anode materials, represented by silicon (Si) (theoretical specific capacity > 3500 mAh / g), have become the core for realizing next-generation high-energy-density batteries due to their significantly higher theoretical specific capacity than traditional graphite.
[0003] However, high-capacity silicon materials undergo violent lithium insertion / delithiation reactions during the charging and discharging process of lithium-ion batteries, accompanied by extreme volume expansion and contraction of more than 300%. This repeated and violent volume change can lead to the pulverization and shedding of active material particles, damaging the overall structural integrity of the electrode.
[0004] Therefore, it is necessary to improve traditional technologies. Summary of the Invention
[0005] Based on this, this application provides a conductive binder that can effectively alleviate volume expansion, a method for preparing the same, an electrode slurry, an electrode, and a lithium-ion battery.
[0006] The technical solution to the above-mentioned technical problems in this application is as follows.
[0007] The first aspect of this application provides a method for preparing a conductive adhesive, comprising the following steps:
[0008] A modified carbon material is prepared by mixing carboxylated carbon material and vinyl compound and carrying out an acylation reaction; the structure of the vinyl compound is: H2C=CH-LXH, wherein X is selected from imino or ether bond, and L is selected from C1~C4 alkylene;
[0009] The modified carbon material, acrylic monomers, and initiator are mixed and polymerized.
[0010] In some embodiments, in the method for preparing the conductive adhesive, L is selected from C1-C2 alkylene groups.
[0011] In some embodiments, in the method for preparing the conductive adhesive, the vinyl compound is selected from at least one of allylamine, 3-buten-1-amine, and allyl alcohol.
[0012] In some embodiments, in the method for preparing the conductive adhesive, the mass ratio of the modified carbon material to the acrylic monomer is 1:3~8.
[0013] In some embodiments, in the method for preparing the conductive adhesive, the acrylic monomer includes at least one of hard monomers and soft monomers, the hard monomer includes at least one of acrylic acid and methacrylic acid, and the soft monomer includes at least one of butyl acrylate, hydroxyethyl acrylate and polyethylene glycol acrylate.
[0014] In some embodiments, in the method for preparing the conductive adhesive, the acrylic monomer includes a hard monomer and a soft monomer, and the mass ratio of the hard monomer to the soft monomer is 1:2~6.
[0015] In some embodiments, in the method for preparing the conductive binder, the carbon material in the carboxylated carbon material includes at least one of carbon nanotubes and graphene.
[0016] In some embodiments, in the method for preparing the conductive adhesive, the carbon material in the carboxylated carbon material includes carbon nanotubes and graphene, and the mass ratio of the carbon nanotubes to the graphene is 1:0.2~2.
[0017] In some embodiments, the acylation reaction temperature in the method for preparing the conductive adhesive is 20°C to 60°C.
[0018] And / or, prior to the acylation reaction, the method further includes: mixing the carboxylated carbon material with an aprotic polar solvent, adding a coupling agent under an inert atmosphere, and activating the carboxyl groups in the carboxylated carbon material.
[0019] In some embodiments, the initiator in the method for preparing the conductive adhesive includes persulfate;
[0020] And / or, the polymerization reaction is carried out at a temperature of 70°C to 85°C.
[0021] In some embodiments, the method for preparing the conductive adhesive further includes, after the polymerization reaction is completed, adjusting the pH of the reaction solution after the polymerization reaction to 7-8 using an alkaline lithium salt.
[0022] A second aspect of this application provides a conductive adhesive comprising a modified carbon material and an acrylic polymer. The modified carbon material comprises a carbon material and functional groups attached to the carbon material. The functional groups have the structure: H2C=CH-LX-CO-, where X is selected from imino or ether bonds, and L is selected from C1-C4 alkylene groups. The vinyl groups in the functional groups are chemically bonded to the acrylic polymer.
[0023] A third aspect of this application provides an electrode paste, including a conductive binder prepared by the method for preparing the conductive binder provided in the first aspect or a conductive binder provided in the second aspect.
[0024] A fourth aspect of this application provides an electrode comprising a current collector and an active layer disposed on at least one surface of the current collector, wherein the active layer comprises a conductive binder prepared by the method of preparing the conductive binder provided in the first aspect or a conductive binder provided in the second aspect; or, the active layer is prepared using an electrode slurry provided in the third aspect.
[0025] In some embodiments, the electrode is a negative electrode, and the active layer includes a negative electrode active material, which includes a silicon-based material; optionally, the mass of the silicon-based material accounts for 10% to 30% of the total mass of the active layer; optionally, the silicon-based material includes at least one of elemental silicon, silicon oxide, and silicon-carbon composite.
[0026] The fifth aspect of this application provides a lithium-ion battery, including the electrodes provided in the fourth aspect.
[0027] The method for preparing the conductive adhesive of this application involves mixing carboxylated carbon material and vinyl compounds for an acylation reaction. The vinyl compounds contain amino or hydroxyl groups, which react with the carboxyl groups in the carbon material to generate amide or ester bonds. Vinyl-substituted carbamoyl groups or vinyl-substituted oxycarbonyl groups are then constructed on the carbon material to obtain a modified carbon material. This modified carbon material serves as the framework for a chemical reaction, on which acrylic monomers are initiated to undergo in-situ polymerization and crosslinking, forming a covalently linked, three-dimensional interpenetrating conductive-adhesive integrated network. The conductive network and the polyacrylic adhesive network undergo synergistic elastic deformation, thereby effectively mitigating volume expansion. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the embodiments of this application and to more completely understand this application and its beneficial effects, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 This is a SEM image of the electrode after 300 cycles in Example 2;
[0030] Figure 2 The image shows the SEM image of the electrode after 300 cycles for Comparative Example 1. Detailed Implementation
[0031] The present application will be further described in detail below with reference to the embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the disclosure of the present application more thorough and comprehensive.
[0032] It should also be understood that this application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various alterations or modifications without departing from the spirit of this application, and the resulting equivalent forms also fall within the protection scope of this application. For example, features described or illustrated as part of one embodiment can be combined in a suitable manner in another embodiment to produce new embodiments. Furthermore, numerous specific details are set forth in the following description to provide a fuller understanding of this application; it should be understood that this application can be implemented without one or more of these details.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for descriptive purposes only and is not intended to be limiting of the application.
[0034] Unless otherwise stated or in case of contradiction, the terms or phrases used herein shall have the following meanings:
[0035] In this application, the terms "multiple", "various", "multiple times", etc., unless otherwise specified, refer to a quantity greater than or equal to 2. For example, "one or more" means one or more than or equal to two.
[0036] The terms “combinations of,” “any combination of,” and “any combination of” used in this article include all suitable combinations of any two or more of the listed items.
[0037] In this document, the term "suitable" as used in "suitable combination", "suitable method", "any suitable method", etc., refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.
[0038] In this document, terms such as "preferred," "better," "more suitable," and "ideal" are merely descriptions of more effective implementation methods or embodiments, and should be understood not to limit the scope of protection of this application. If multiple "preferred" terms appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "preferred" term shall be independent.
[0039] In this application, terms such as "further," "even further," and "particularly" are used to describe purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0040] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0041] In this application, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0042] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0043] In this application, when numerical intervals (i.e., numerical ranges) are mentioned, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include numerical interval types such as percentage intervals, ratio intervals, and proportion intervals.
[0044] Unless otherwise specified, the temperature parameters in this application are permitted to be either constant-temperature treatment or variations within a certain temperature range. It should be understood that the constant-temperature treatment allows temperature fluctuations within the precision range of the instrument control, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.
[0045] In this application, the terms "room temperature" or "normal temperature" generally refer to 4℃~35℃, for example, 20℃±5℃. In some embodiments of this application, "room temperature" or "normal temperature" refers to 10℃~30℃. In some embodiments of this application, "room temperature" or "normal temperature" refers to 20℃~30℃.
[0046] In this application, if the unit of a data range is only followed by the right endpoint, it indicates that the units of the left and right endpoints are the same. For example, 3~5 h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).
[0047] The mass or weight of the relevant components mentioned in this application specification can refer not only to the specific content of each component, but also to the proportional relationship of mass or weight between the components. Therefore, any scaling up or down of the content of the relevant components according to this application specification is within the scope of disclosure in this application specification. Specifically, the mass or weight mentioned in the embodiments of this application can be units known in the chemical industry such as μg, mg, g, and kg.
[0048] Regarding the issue of pulverization and detachment of active material particles due to repeated and drastic volume changes during the charging and discharging process of lithium-ion batteries, binder systems such as polyacrylic acid (PAA) and carboxymethyl cellulose / styrene-butadiene rubber (CMC / SBR) can, to some extent, buffer volume expansion through the interaction between their functional groups and the surface of the active material. However, when binders and conductive agents are physically mixed in the electrode, this physical connection, which relies on weak van der Waals forces, is easily disrupted when the active material particles undergo drastic expansion, leading to conductive network failure and electrode structure collapse.
[0049] Furthermore, silicon materials have low intrinsic electrical conductivity. The combination of volume effect and low conductivity, two core problems, significantly reduces the cycle stability and rate performance of silicon-based anode batteries, resulting in severe capacity decay during charge and discharge. Carbon nanotubes (CNTs) and graphene have good electrical conductivity, but their connection with binders is only through physical entanglement or adsorption. During the repeated expansion and contraction of the active material particles, the binder deforms, and the interface between the conductive agent and the binder / active material is prone to sliding and detachment, leading to interruption of the electron transport path.
[0050] One embodiment of this application provides a method for preparing a conductive adhesive, comprising the following steps:
[0051] Step S100: The carboxylated carbon material and the vinyl compound are mixed and subjected to an acylation reaction to prepare the modified carbon material; the structure of the vinyl compound is: H2C=CH-LXH, where X is selected from imino or ether bond, and L is selected from C1~C4 alkylene.
[0052] A acylation reaction is carried out by mixing carboxylated carbon materials and vinyl compounds. The vinyl compounds contain amino or hydroxyl groups, which react with the carboxyl groups in the carbon materials to form amide or ester bonds. Modified carbon materials are obtained by constructing vinyl-substituted carbamoyl groups or vinyl-substituted oxycarbonyl groups on the carbon materials.
[0053] It can be understood that carboxylated carbon materials refer to carbon materials with carboxyl groups attached; imino refers to "-NH-", and ether bond refers to "-O-"; alkylene refers to a divalent group formed by removing two hydrogen atoms from an alkane molecule, and C1~C4 alkylene refers to a group formed by removing two hydrogen atoms from an alkane molecule with 1~4 carbon atoms, including one of methylene (C1 alkylene, -CH2-), ethylene (C2 alkylene), propylene (C3 alkylene), and butylene (C4 alkylene); further, ethylene includes 1,2-ethylene (-CH2CH2-) and 1,1-ethylene (-CH2CH2-). One of the following; propylidene includes, but is not limited to, 1,3-propylidene (-CH2CH2CH2-) and isopropylidene ( One of the following: butylene; including but not limited to 1,4-butylene (-CH2CH2CH2CH2-), etc.
[0054] In some of these examples, in step S100, L is selected from C1-C2 alkylene groups.
[0055] In some of these examples, in step S100, the vinyl compound is selected from at least one of allylamine (H2C=CH-CH2-NH2), 3-buten-1-amine (H2C=CH-CH2-CH2-NH2), and allyl alcohol (H2C=CH-CH2-OH).
[0056] It is understood that carbon materials include, but are not limited to, at least one of carbon nanotubes, graphene, and carbon nanofibers.
[0057] In some examples, in step S100, the carbon material in the carboxylated carbon material includes at least one of carbon nanotubes and graphene. It is understood that carbon nanotubes include, but are not limited to, at least one of multi-walled carbon nanotubes, oligo-walled carbon nanotubes, and single-walled carbon nanotubes; graphene includes, but is not limited to, at least one of physically processed graphene and redox graphene.
[0058] In some of these examples, in step S100, the carbon material in the carboxylated carbon material includes carbon nanotubes and graphene.
[0059] In some examples, in step S100, the mass ratio of carbon nanotubes to graphene is 1:0.2 to 2. It is understood that the mass ratio of carbon nanotubes to graphene includes, but is not limited to, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, and 1:2; in some examples, it can be any two of these point values forming a range.
[0060] In some of these examples, in step S100, the carbon nanotubes have a diameter of 10 nm to 20 nm and a length of 10 μm to 30 μm.
[0061] In some of these examples, in step S100, the graphene sheet diameter is 1 μm to 10 μm. It is understood that the graphene sheet diameter includes, but is not limited to, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.
[0062] In some examples, the acylation reaction temperature in step S100 is 20℃~60℃. It is understood that the acylation reaction temperature includes, but is not limited to, 20℃, 22℃, 24℃, 26℃, 28℃, 30℃, 32℃, 34℃, 36℃, 38℃, 40℃, 42℃, 44℃, 46℃, 48℃, 50℃, 52℃, 54℃, 56℃, 58℃, and 60℃; in some examples, it can be any two of these point values forming a range.
[0063] In some examples, step S100 further includes, prior to the acylation reaction, mixing the carboxylated carbon material with an aprotic polar solvent and adding a coupling agent under an inert atmosphere to activate the carboxyl groups in the carboxylated carbon material. It can be understood that the carboxyl groups in the carboxylated carbon material are activated before the vinyl compound is added for the acylation reaction.
[0064] Optionally, the aprotic polar solvent includes N,N-dimethylformamide (DMF).
[0065] Optionally, the coupling agent includes at least one of N-hydroxysuccinimide (NHS) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC).
[0066] Optionally, the inert atmosphere includes, but is not limited to, nitrogen or argon.
[0067] In some of these examples, step S100 involves the following steps:
[0068] Step S110: Add carbon material to acid solution and stir at 60℃~80℃ to prepare carboxylated carbon material.
[0069] It can be understood that the carbon material in step S110 is the original carbon material, the uncarboxylated carbon material; after the treatment in step S110, oxygen-containing groups such as carboxyl groups are introduced on the surface.
[0070] In some examples, in step S110, the acid solution includes at least one of concentrated sulfuric acid and concentrated nitric acid. Optionally, the acid solution includes concentrated sulfuric acid and concentrated nitric acid. Optionally, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 2 to 4:1. It is understood that the volume ratio of concentrated sulfuric acid to concentrated nitric acid includes, but is not limited to, 2:1, 3:1, and 4:1.
[0071] It is understood that in step S110, the stirring temperature includes, but is not limited to, 60℃, 61℃, 62℃, 63℃, 64℃, 65℃, 66℃, 67℃, 68℃, 69℃, 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃, and 80℃. Optionally, the stirring time is 2 h to 4 h.
[0072] It is understandable that when the carbon material in the carboxylated carbon material in step S100 includes both carbon nanotubes and graphene, the carbon nanotubes and graphene are carboxylated separately.
[0073] Step S200: Mix the modified carbon material, acrylic monomer and initiator to carry out the polymerization reaction.
[0074] It is understandable that step S200 involves mixing modified carbon materials, acrylic monomers, and initiators for in-situ polymerization.
[0075] The modified carbon material obtained in step S100 is used as the framework for the chemical reaction. The framework has vinyl-substituted carbamoyl or vinyl-substituted oxycarbonyl active sites. Acrylic monomers are initiated to undergo in-situ polymerization and crosslinking on the framework to form a covalently linked, three-dimensional interpenetrating conductive-adhesive integrated network. The conductive network and the polyacrylic adhesive network cooperate in elastic deformation, thereby effectively mitigating volume expansion.
[0076] In-situ polymerization enables the binder to form a tight molecular-level coating on the surface of the modified carbon material, effectively inhibiting the pulverization and detachment of the modified carbon material. Using the prepared conductive binder in electrode fabrication helps guide the formation of a more uniform and denser solid electrolyte interphase (SEI) film on the surface of the active material, reducing irreversible electrolyte consumption and thus improving the initial coulombic efficiency. The preparation method of this application is highly compatible with existing lithium-ion battery slurry preparation and coating processes and can simplify the slurry preparation process.
[0077] Unlike traditional binders and conductive agents that rely on weak van der Waals forces or physical entanglement, the covalent bonding in this application ensures that when the volume of the active material changes drastically (>300%), the conductive network can elastically deform in tandem with the binder network without interfacial slippage, thus fundamentally maintaining the integrity of the electron transport path.
[0078] In some examples, in step S200, the mass ratio of the modified carbon material to the acrylic monomer is 1:3 to 8. It is understood that the mass ratio of the modified carbon material to the acrylic monomer includes, but is not limited to, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4, 1:4.2, 1:4.4, 1:4.6, 1:4.8, 1:5, 1:5.2, 1:5.4, 1:5.6, 1:5.8, 1:6, 1:6.2, 1:6.4, 1:6.6, 1:6.8, 1:7, 1:7.2, 1:7.4, 1:7.6, 1:7.8, and 1:8; in some examples, it can be any two of these values forming a range. Optionally, the mass ratio of the modified carbon material to the acrylic monomer is 1:4 to 7. Optionally, the mass ratio of the modified carbon material to the acrylic monomer is 1:5 to 6. By controlling the mass ratio of modified carbon materials to acrylic monomers, the peel strength and conductivity of conductive adhesives can be further improved.
[0079] It is understood that acrylic monomers include at least one of acrylic monomers and acrylate monomers.
[0080] In some of these examples, in step S200, the acrylic monomers include at least one of hard monomers and soft monomers.
[0081] Alternatively, the hard monomer includes at least one of acrylic acid and methacrylic acid.
[0082] Optionally, the soft monomer includes at least one of butyl acrylate, hydroxyethyl acrylate, and polyethylene glycol acrylate.
[0083] In some of these examples, in step S200, the acrylic monomers include hard monomers and soft monomers.
[0084] In some examples, in step S200, the mass ratio of hard monomers to soft monomers is 1:2 to 6. It is understood that the mass ratio of hard monomers to soft monomers includes, but is not limited to, 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4, 1:4.2, 1:4.4, 1:4.6, 1:4.8, 1:5, 1:5.2, 1:5.4, 1:5.6, 1:5.8, and 1:6; in some examples, it can be any two of these point values forming a range.
[0085] In some of these examples, in step S200, the initiator includes a persulfate; alternatively, the persulfate includes at least one of ammonium persulfate and potassium persulfate.
[0086] In some examples, in step S200, the polymerization temperature is 70℃~85℃. It is understood that the polymerization temperature includes, but is not limited to, 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃, 80℃, 81℃, 82℃, 83℃, 84℃, and 85℃; in some examples, it can be any two of these point values forming a range.
[0087] In some examples, in step S200, the system in which the polymerization reaction takes place also includes at least one of a dispersant and a solvent. Optionally, the dispersant includes sodium dodecyl sulfate (SDS) and sodium dodecyl sulfonate (SLS). Optionally, the solvent includes water.
[0088] In some of these examples, step S200 includes the following steps:
[0089] A suspension is prepared by mixing a dispersant and water, and then adding a modified carbon material.
[0090] Acrylic monomers and initiators are added sequentially to the suspension, and polymerization is carried out at 70℃~85℃.
[0091] In some examples, after the polymerization reaction in step S200 is completed, the following steps are also included:
[0092] Step S300: Adjust the pH of the reaction solution after polymerization to 7-8 using alkaline lithium salt.
[0093] Optionally, the alkaline lithium salt includes at least one of lithium hydroxide and lithium carbonate. Further, the alkaline lithium salt includes lithium hydroxide; thus, the acrylic units on the polymer chain can be converted into the lithium salt form (lithium polyacrylate), which is its active form as a binder in the battery.
[0094] The conductive binder preparation method provided in this application transforms the conductive agent from a passive physical additive into a "skeleton" participating in chemical reactions. It integrates conductive and adhesive functions at the molecular level, deeply coupling the conductive network and the adhesive network through strong chemical bonds to form an integrated network system with high conductivity, high elasticity, and strong interfacial bonding. This system can maintain structural integrity and functional stability throughout the entire charge-discharge cycle of the electrode, fundamentally solving the core problems of electrode pulverization, conductive network failure, and short cycle life caused by volume changes during the charge-discharge process of the negative electrode.
[0095] One embodiment of this application provides a conductive adhesive, prepared using the method described above. Another embodiment of this application provides a conductive adhesive comprising a modified carbon material and an acrylic polymer. The modified carbon material includes carbon material and functional groups attached to the carbon material. The structure of the functional groups is: H2C=CH-LX-CO-, where X is selected from imino or ether bonds, and L is selected from C1-C4 alkylene groups. The vinyl groups in the functional groups are chemically bonded to the acrylic polymer.
[0096] It can be understood that acrylic polymers are polymers of acrylic acid and its derivatives, including but not limited to acrylic acid, methacrylic acid or their esters.
[0097] In some examples, in the conductive binder, acrylic polymers are chemically bonded to modified carbon materials and coated onto the surface of the modified carbon materials. This effectively inhibits the pulverization and detachment of active material particles.
[0098] In some of these examples, the conductive binder is prepared by in-situ polymerization of modified carbon materials and acrylic polymer monomers.
[0099] In some of these examples, the glass transition temperature (Tg) of the conductive adhesive is 40°C to 70°C.
[0100] One embodiment of this application provides an electrode paste, comprising a conductive binder prepared by the above-described method for preparing conductive binders or the above-described conductive binder.
[0101] The electrode slurry contains the aforementioned conductive binder. After being coated onto the current collector to form the corresponding electrode film, it exhibits good conductivity and interfacial adhesion, realizing an integrated conductive-bonding network for the electrode. This allows the slurry to improve the rate capability and cycle stability of the battery when applied to a battery.
[0102] In some of these examples, the electrode paste is a negative electrode paste. Furthermore, the electrode paste may also include a negative electrode active material.
[0103] In some examples, the negative electrode active material in the electrode paste includes, but is not limited to, silicon-based materials. Optionally, the silicon-based material accounts for 10% to 30% of the total mass of the active layer. Optionally, the silicon-based material includes at least one of elemental silicon, silicon oxide compounds, and silicon-carbon composites.
[0104] In some examples, the negative electrode active material in the electrode slurry also includes graphite. Optionally, the mass ratio of silicon-based material to graphite is 0.1 to 0.4:1.
[0105] In some of these examples, the electrode slurry also includes a dispersant. Optionally, the dispersant includes sodium carboxymethyl cellulose.
[0106] One embodiment of this application provides an electrode comprising a conductive binder prepared by the above-described method for preparing conductive binders, the above-described conductive binder, or an electrode slurry prepared using the above-described electrode slurry.
[0107] The electrode provided in this application, including the aforementioned conductive binder, has a good conductive network and bonding network, resulting in a lower interface resistance and higher peel strength. When applied to a battery, it can improve the battery's rate capability and cycle stability.
[0108] In some examples, the electrode includes a current collector and an active layer disposed on at least one surface of the current collector. The active layer includes a conductive adhesive prepared by the above-described method for preparing the conductive adhesive, or the above-described conductive adhesive, or the active layer is prepared using the above-described electrode slurry.
[0109] In some of these examples, the electrode is a negative electrode, and the active layer comprises a negative electrode active material, which may be a silicon-based material.
[0110] Optionally, the mass of the silicon-based material accounts for 10% to 30% of the total mass of the active layer.
[0111] Optionally, the silicon-based material includes at least one of elemental silicon, silicon oxides, and silicon-carbon composites.
[0112] In some examples, the negative electrode active material also includes graphite. Optionally, the mass ratio of silicon-based material to graphite is 0.1 to 0.4:1.
[0113] By achieving covalent bonding between the conductive network and the binder network at the molecular scale, an integrated three-dimensional "core-shell-network" structure is formed, endowing the electrode with mechanical toughness and electrochemical stability, exhibiting a significant synergistic enhancement effect. A strong chemical bond connects the conductive agent and the binder, allowing the entire integrated network to deform synergistically and elastically, effectively buffering volume changes of over 300% in the active material. Compared to traditional physical mixing systems, the electrode of this application shows significantly improved capacity retention and effective control of electrode thickness expansion after 300 cycles.
[0114] One embodiment of this application provides a lithium-ion battery including the electrodes described above.
[0115] The lithium-ion battery provided in this application, including the aforementioned electrodes, can impart high rate capability and cycle stability to the lithium-ion battery.
[0116] The present application will be described in further detail below with reference to specific embodiments, but the embodiments of the present application are not limited thereto.
[0117] Example 1
[0118] (1) Preparation of modified carbon materials
[0119] Preparation of modified carbon nanotubes (V-CNTs):
[0120] S1: By mass, 10 parts of carbon nanotubes (oligowalled carbon nanotubes, diameter 10 nm~20 nm, length 10 μm~30 μm) were added to 100 parts of a mixed acid of concentrated sulfuric acid / concentrated nitric acid (3:1, v / v). After reacting with magnetic stirring at 70 °C for 3 h, the reactants were washed with deionized water by centrifugation until neutral, and then dried under vacuum at 80 °C for 12 h to obtain carboxylated carbon nanotubes (CNTs-COOH).
[0121] S2: By mass, 5 parts of CNTs-COOH were dispersed in 150 parts of DMF and sonicated for 30 minutes. 11.5 parts of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 7 parts of N-hydroxysuccinimide were added to the dispersion and stirred at room temperature for 2 hours to activate the carboxyl groups. 5 parts of allylamine were slowly added dropwise and the reaction was carried out at 50°C under nitrogen protection for 24 hours. The reaction product was washed three times by centrifugation with ethanol and then dried under vacuum at 60°C for 24 hours to obtain modified carbon nanotubes (V-CNTs, H2C=CH-CH2-NH-CO-carbon nanotubes).
[0122] The preparation of modified graphene (V-Gne, H2C=CH-CH2-NH-CO-graphene) is the same as the preparation of modified carbon nanotubes (V-CNTs) described above, except that the carbon nanotubes are replaced with graphene. Carboxylated graphene is prepared in S1 and modified graphene is prepared in S2.
[0123] (2) In-situ polymerization to construct an integrated conductive binder network
[0124] S3: By mass, in a four-necked flask equipped with a stirrer, reflux condenser and nitrogen delivery tube, add 1000 parts of deionized water and 10 parts of emulsifier SDS, then add 50 parts of modified carbon nanotubes prepared in step (1), stir at 2000 r / min for 30 min to disperse them evenly; then add 10 parts of modified graphene prepared in step (1), stir at 2000 r / min for 30 min to disperse them evenly.
[0125] S4: By mass, add 72 parts of acrylic acid (AA) and 256 parts of butyl acrylate (BA), then add 1.5 parts of initiator KPS, heat the system to 80°C, and react for 4 h; after the reaction is complete, cool to room temperature; wherein, the mass ratio of hard monomer to soft monomer is 1:3.56, and the mass ratio of modified carbon material to acrylic monomer is approximately 1:5.5.
[0126] S5: The pH of the adhesive solution was adjusted to 7.5 by slow titration with 1.0 M LiOH aqueous solution, resulting in a structurally functional conductive adhesive with a solid content of approximately 25% and a uniform black appearance.
[0127] Example 2
[0128] The difference from Example 1 is that the oligowalled carbon nanotubes in Example 1 are replaced with single-walled carbon nanotubes.
[0129] Example 3
[0130] The difference from Example 1 is that the graphene in Example 1 is replaced with reduced graphene oxide.
[0131] Example 4
[0132] The difference from Example 1 is that the allylamine in step S2 of Example 1 is replaced with an equal mass of allyl alcohol to prepare modified carbon nanotubes (H2C=CH-CH2-O-CO-carbon nanotubes) and modified graphene (H2C=CH-CH2-O-CO-graphene).
[0133] Example 5
[0134] The difference from Example 1 is that acrylic acid is omitted, and the 72 parts of acrylic acid and 256 parts of butyl acrylate in step S4 of Example 1 are replaced with 328 parts of butyl acrylate.
[0135] Example 6
[0136] The difference from Example 1 is that the modified graphene is omitted, and the 50 parts of modified carbon nanotubes and 10 parts of modified graphene in step S3 of Example 1 are replaced with 60 parts of modified carbon nanotubes.
[0137] Example 7
[0138] The difference from Example 1 is that "72 parts acrylic acid (AA) and 256 parts butyl acrylate (BA)" in step S4 of Example 1 are replaced with "40 parts acrylic acid and 140 parts butyl acrylate"; the mass ratio of modified carbon material to acrylic monomer is 1:3.
[0139] Example 8
[0140] The difference from Example 1 is that "72 parts acrylic acid (AA) and 256 parts butyl acrylate (BA)" in step S4 of Example 1 are replaced with "105 parts acrylic acid and 375 parts butyl acrylate"; the mass ratio of modified carbon material to acrylic monomer is 1:8.
[0141] Example 9
[0142] The difference from Example 1 is as follows:
[0143] S1: In the preparation of modified carbon nanotubes (V-CNTs), the oligowalled carbon nanotubes in Example 1 are replaced with multiwalled carbon nanotubes;
[0144] S2: By replacing allylamine with an equal number of 3-buten-1-amine, H2C=CH-CH2-CH2-NH-CO-carbon nanotubes and H2C=CH-CH2-CH2-NH-CO-graphene were prepared respectively.
[0145] S4: By mass, add 48 parts of methacrylic acid and 280 parts of hydroxyethyl acrylate, then add 1.5 parts of initiator KPS, heat the system to 80°C, and react for 4 h; after the reaction is complete, cool to room temperature; wherein, the mass ratio of hard monomer to soft monomer is 1:5.83, and the mass ratio of modified carbon material to acrylic monomer is approximately 1:5.5.
[0146] Comparative Example 1
[0147] Mix 50 parts of carbon nanotubes, 10 parts of graphene, and polyacrylic acid (PAA) binder.
[0148] Comparative Example 2
[0149] Mix 50 parts of modified carbon nanotubes, 10 parts of modified graphene, and polyacrylic acid (PAA) binder prepared in step (1) of Example 1.
[0150] Comparative Example 3
[0151] The difference from Example 1 is that S1 and S2 in step (1) are omitted, and the modified carbon nanotubes in step (2) of Example 1 are replaced with carbon nanotubes of equal mass, and the modified graphene is replaced with graphene of equal mass.
[0152] Comparative Example 4
[0153] The difference from Example 1 is that step (1) S2 is omitted, the modified carbon nanotubes in step (2) of Example 1 are replaced with carboxylated carbon nanotubes of equal mass, and the modified graphene is replaced with carboxylated graphene of equal mass.
[0154] Comparative Example 5
[0155] The difference from Example 1 is that the modified carbon nanotubes in step (2) of Example 1 are replaced with carbon nanotubes containing hydroxyl and carboxyl groups of equal mass, and the modified graphene is replaced with graphene containing hydroxyl and carboxyl groups of equal mass.
[0156] The conductive binders prepared in each embodiment and comparative example were mixed uniformly with silicon, graphite, sodium carboxymethyl cellulose, and deionized water at the same mass ratio, and dispersed at a high speed of 3000 rpm for 2 hours to prepare a uniform negative electrode slurry. This slurry was then uniformly coated onto a current collector copper foil, and after drying, rolling, and slitting, a negative electrode sheet was obtained. The resistivity and peel strength of the electrode sheet were tested. The negative electrode sheet was assembled with a ternary lithium positive electrode sheet and a separator to prepare a battery cell. After liquid injection, formation, and capacity testing, a lithium-ion battery was obtained. The initial coulombic efficiency, capacity performance, and rate performance of the battery cell were tested.
[0157] Resistivity: Tested using a four-probe resistance meter;
[0158] Peel strength: tested using a servo-driven tensile testing machine, 180° peel test;
[0159] Initial coulombic efficiency: tested using an electrochemical workstation;
[0160] Capacity performance: Tested using an electrochemical workstation; Capacity retention after 300 cycles = (Ratio of discharge capacity after 300 charge-discharge cycles to initial discharge capacity) × 100%;
[0161] Rate performance: tested using an electrochemical workstation;
[0162] The resistivity and peel strength of the electrode, the initial coulombic efficiency of the cell, and the capacity retention after 300 cycles are shown in Table 1.
[0163] Table 1
[0164]
[0165] As shown in Table 1, compared with the comparative example, each embodiment mixes carboxylated carbon material with vinyl compounds containing amino or hydroxyl groups for acylation reaction, and uses the prepared modified carbon material as the backbone of the chemical reaction. On this backbone, acrylic monomers are initiated to undergo in-situ polymerization and crosslinking, which can effectively reduce the resistivity of conductive adhesive and improve the peel strength of conductive adhesive.
[0166] In Example 1, an allylamine-modified carbon material was polymerized in situ with acrylic monomers to obtain a conductive binder. When applied to a silicon-based anode, the electrode resistivity was only 13 Ω·cm, the peel strength reached 28.8 N / m, the initial coulombic efficiency was 97.2%, and the capacity retention rate after 300 cycles was 92.1%.
[0167] Comparative Examples 1 and 2 did not use in-situ polymerization. Comparative Example 1 used unmodified carbon material to be physically mixed directly with the polymer binder PAA, while Comparative Example 2 used modified carbon material to be physically mixed directly with the polymer binder PAA. The resulting conductive binders had higher resistivity and lower peel strength. This indicates that simple physical mixing is difficult to form a stable conductive network, leading to increased resistivity, and also weakens the bonding interface force, resulting in lower peel strength. This highlights the significant advantages of in-situ polymerization in improving the overall conductivity and bonding performance.
[0168] The difference between Comparative Examples 3-5 and Example 1 is that the carbon materials not modified with specific groups (allylamine, allyl alcohol) were used. In-situ polymerization of unmodified carbon materials, carboxylated carbon materials, or carbon materials containing hydroxyl and carboxyl groups with acrylic monomers resulted in conductive adhesives with lower peel strength and higher resistivity compared to Example 1. This indicates that even with in-situ polymerization of carbon materials with acrylic monomers, relying solely on the carbon materials themselves or their inherent hydroxyl and carboxyl groups, it is still impossible to achieve high-strength chemical bonding between the carbon materials and the polymer matrix. The interfacial bonding effect is poor, making it difficult to construct a continuous and unobstructed conductive network. Therefore, it is proven that modifying carbon materials with specific active groups such as allylamine and allyl alcohol is a necessary condition for improving interfacial bonding, optimizing conductive pathways, and simultaneously improving peel strength and conductivity.
[0169] Furthermore, as shown in Examples 1 and 4, the resistivity of amide bond modification (allylamine) is reduced by 32% compared with that of ester bond modification (allyl alcohol), proving that amide bonds have better chemical stability and interfacial bonding in the electrolyte environment.
[0170] As can be seen from Examples 1 and 5, combining hard monomers and soft monomers, along with other components, can effectively improve the peel strength of conductive adhesives; the carboxyl groups in the hard monomers are key sites for the formation of strong hydrogen bonds / covalent bonds between the polymer and the silicon surface.
[0171] As can be seen from Examples 1 and 6, combining modified carbon nanotubes and modified graphene to form a "point-surface" complementary conductive network can effectively reduce the resistivity of the conductive binder.
[0172] As can be seen from Examples 1 and 7-8, by controlling the mass ratio of modified carbon material to acrylic monomers, the peel strength and conductivity of conductive adhesives can be effectively improved.
[0173] The rate capability is shown in Table 2.
[0174] Table 2
[0175]
[0176] like Figure 1 and Figure 2 As shown, after 300 cycles, the surface of the negative electrode particles in Comparative Example 1 was rough, showing obvious breakage and pulverization; while the surface of the silicon negative electrode particles in Example 2 was relatively smooth and the structure was relatively complete, with no obvious breakage and pulverization. This proves that the in-situ polymerization of the modified carbon material binder in this application can improve the stability of the electrode structure and enhance the cycle performance of the silicon negative electrode to a certain extent compared with the simple mixing of carbon material and binder.
[0177] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0178] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a conductive adhesive, characterized in that, Includes the following steps: A modified carbon material is prepared by mixing carboxylated carbon material and vinyl compound and carrying out an acylation reaction; the vinyl compound is selected from allylamine; the carbon material in the carboxylated carbon material includes carbon nanotubes and graphene, and the carbon nanotubes include at least one of oligowalled carbon nanotubes and singlewalled carbon nanotubes; The modified carbon material, acrylic monomers, and initiator are mixed and subjected to a polymerization reaction. The acrylic monomers include hard monomers and soft monomers. The hard monomers include at least one of acrylic acid and methacrylic acid. The soft monomers include at least one of butyl acrylate, hydroxyethyl acrylate, and polyethylene glycol acrylate. The mass ratio of the hard monomers to the soft monomers is 1:2 to 5. The mass ratio of the modified carbon material to the acrylic monomers is 1:4 to 7.
2. The method for preparing the conductive adhesive as described in claim 1, characterized in that, The mass ratio of the modified carbon material to the acrylic monomer is 1:5~6.
3. The method for preparing the conductive adhesive as described in claim 1, characterized in that, The carbon nanotubes have a diameter of 10 nm to 20 nm and a length of 10 μm to 30 μm; the graphene sheets have a diameter of 1 μm to 10 μm.
4. The method for preparing the conductive adhesive as described in claim 3, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The mass ratio of the hard monomer to the soft monomer is 1:3~4; (2) The mass ratio of the carbon nanotubes to the graphene is 1:0.2~2.
5. The method for preparing the conductive adhesive according to any one of claims 1 to 4, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The temperature of the acylation reaction is 20℃~60℃; (2) Before the acylation reaction, the method further includes: mixing the carboxylated carbon material with an aprotic polar solvent, and adding a coupling agent under an inert atmosphere to activate the carboxyl groups in the carboxylated carbon material; (3) The initiator includes persulfate; (4) The polymerization reaction temperature is 70℃~85℃; (5) After the polymerization reaction is completed, the method further includes: adjusting the pH value of the reaction solution after the polymerization reaction to 7-8 using alkaline lithium salt.
6. A conductive adhesive, characterized in that, The invention comprises modified carbon materials and acrylic polymers. The modified carbon materials include carbon materials and functional groups attached to the carbon materials. The structure of the functional groups is: H2C=CH-LX-CO-, where X is selected from imino and L is selected from C1 alkylene. The vinyl groups in the functional groups are chemically bonded to the acrylic polymers. The carbon materials include carbon nanotubes and graphene. The carbon nanotubes include at least one of oligowalled carbon nanotubes and single-walled carbon nanotubes. The monomers for preparing the acrylic polymers include hard acrylic monomers and soft acrylic monomers. The hard monomers include at least one of acrylic acid and methacrylic acid. The soft monomers include at least one of butyl acrylate, hydroxyethyl acrylate, and polyethylene glycol acrylate. The mass ratio of the hard monomers to the soft monomers is 1:2~5. The mass ratio of the modified carbon materials to the acrylic monomers is 1:4~7.
7. An electrode paste, characterized in that, The conductive adhesive includes the conductive adhesive prepared by the method described in any one of claims 1 to 5, or the conductive adhesive as described in claim 6.
8. An electrode, characterized in that, It includes a current collector and an active layer disposed on at least one surface of the current collector, wherein the active layer comprises a conductive adhesive prepared by the method of preparing the conductive adhesive as described in any one of claims 1 to 5 or a conductive adhesive as described in claim 6; or, the active layer is prepared using the electrode paste as described in claim 7.
9. The electrode as claimed in claim 8, characterized in that, The electrode is a negative electrode, and the active layer includes a negative electrode active material, which includes a silicon-based material.
10. A lithium-ion battery, characterized in that, Includes the electrode as described in any one of claims 8 to 9.
Citation Information
Patent Citations
Crosslinking type conductive binder, negative pole piece and lithium ion battery
CN118978876A
